Implementasi Teknik Animasi Frame by Frame Pada Animasi 2D Sebagai Media Promosi Desa - Surya Ramadan Hasibuan; Dharmawati; Rismayanti (SNASTIKOM, 2023)
Now there are many kinds of promotions that have been made along with the times, animation itself can be used as a form of promotion. The types of promotions that are made are sometimes based on 2 dimensions and 3 dimensions. Various things are promoted, both products and the promotion of tourist objects. In the promotion of tourist objects, it is usual to take places that are rarely known to someone, such as underdeveloped villages but have tourism potential that can attract people's attention, such as culture, daily life, or customs of the place. For 2-dimensional animation itself, there are many methods, one of which is used in this study is frame by frame, where this method is a method that in moving objects must draw objects in each frame, the more objects that are drawn in each frame, the more objects are drawn in each frame. the smoother the resulting animation. The promotion produced in this study, it will be in the form of an animated video file that can be played in a video player application